THE OTHER DOES NOT RESPOND: levinas's answer to blanchot. Issue 3 (4th May 2019) - Bernasconi, Robert
Abstract: Levinas's idea of substitution promotes what sounds at first sight like a full-blown notion of relationality. This is reflected, for example, in his adoption of Rimbaud's phrase "I is an other." But Levinas also insisted that the I is a term that exceeds the relation in the same way that the Other does. Maurice Blanchot questioned these implications in The Writing of the Disaster, but Levinas held fast to his conclusion that this was a "relation without relation, " one of a number of formulations that test our standards of comprehension. In this essay I explore the considerations that led Levinas to adopt these formulations, focusing both on his account of my responsibility, even for the one who persecutes me, and his novel account of "subjectivity."